Caracterização e zoneamento ambiental da reserva particular do patrimônio natural Parque Ecológico João Medeiros (Fazenda Verde, Rondonópolis, MT) - Nardes, Antonia Marilia Medeiros (2005)
This study was undertaken at the Lapa microbasin (Itirapina/ Ipeúna), located in the central Cuestas region of the State of São Paulo, Brazil, with the objective to characterize ichthyofauna composition and longitudinal distribution within the basin and to examine the diversity, richness and equability for each of the 12 sample stations. Sampling took place at the Lapa and Cantagalo streamlets and the Passa Cinco River. The characterization of the area was realized with seasonal data of the limnological and morpho-hydrologic variables, in addition of observation of localized, substratum and vegetation conditions. The relationship between the abiotic factors and the ichthyofauna was also verified. The research was realized in two sampling stages: during the first there were four seasonal samplings from April of 2002 to February of 2003; during the second, there were monthly samplings from July of 2003 to June of 2004, but only for the Corumbataia cuestae, a endemic species in this region, selected for the study of reproductive biology. The research on ichthyofauna revealed the presence of 52 species from 5 orders, 15 families and 34 genera. In term of number of species, abundance and biomass, the orders Characiformes and Silurifromes were most representative. Most of the species collected had a constant occurrence (72%); 18% were accidentals and 10% accessories. The succession of species occurs by addition, from the head to the mouth of the river. Discriminate multivariate analysis revealed that some abiotic characteristics of the streams such as depth, velocity, breadth and altitude are more important for the discrimination of the sampling stations, occurring a gradient from the superior portion (Cuesta) to the inferior (Peripheric Depression). This same gradient was evident on the Correspondence multivariate analysis of specie abundance at each sampling station during the dry and rainy seasons showing the degree of association between the species in the microbasin. The analysis of ichthyofauna similarity (Jaccard and Bray-Curtis) confirms the gradient shown in the multivariate analysis. The length characterization of ten most abundant species showed large length amplitude and ample distribution in the environment. Like the "richness" of species, the Shannon Diversity Index goes up in the direction head to mouth, with the highest values in the Passa Cinco River. For the reproductive biology study, the sample consisted of a total of 377 specimens of C. cuestae, 166 female (44%), 146 males (44%) and 47 non-differentiated (12%). The macro and microscopic characteristics of gonads, in addition to the IGS values allowed the establishment of four gonadal maturation stages for females and males: Maturation, In Reproduction, Spent and Resting. The maturation curve obtained by the monthly distribution of the mean IGS values, the monthly frequency of the gonadal maturation stages and the distribution of frequency of oocytes diameter show that there is a continuous reproductive period and spawning intermittently. The significant association between breeding activity and dry and rainy seasons shows greater intensity in reproduction during the rainy. The first gonadal maturation length for female and male was 2.6 cm of the standard length, determined by the length of the smallest specimen in advanced maturation. The macro and microscopic gonadal analysis, the development of eggs and larvae permitted a discussion about the life strategy of this species which, along with other stream species, are adapted to this environment exposed to high instability. The microbasin is a environment still well conserved, with a great richness of species. The distribution of the species is markedly influenced by abiotic factors.